2017
DOI: 10.1111/jfb.13293
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive biology of Haemulon plumierii in the south‐western Atlantic Ocean's most extensive reefs: implications for fisheries management

Abstract: The reproductive biology of the white grunt Haemulon plumierii was studied from 360 individuals obtained from artisanal fisheries landings in the Abrolhos Bank, Brazil, between August 2010 and March 2012. The overall sex-ratio did not differ significantly from 1:1, although males predominated in larger size classes. β-Binomial modelling of historical sex-ratio data indicated that the catch rate of females has increased in recent years. Females reached maturity at a smaller total length (L ; 214 mm) than males … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 49 publications
(94 reference statements)
2
5
1
Order By: Relevance
“…Based on the results of monthly variation of the relative frequencies of the reproductive phases of gonadal maturity and the mean GSI, for both sexes, it is suggested that the reproductive period of H. plumierii in the study area occurred from February to August, with a spawning peak between March to June. This spawning seasonality coincides with that reported from Jamaica (Munro et al, 1973), the Campeche Bank of Mexico (Darcy, 1983), Florida (Murie & Parkyn, 1999), Venezuela (Palazón-Fernández, 2007, and Brazil (Hoffmann et al, 2017;Shinozaki et al, 2013;Silva, 2015;Souza, 2008). Despite the differences in climatic seasonality between hemispheres, northern Figure 5.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Based on the results of monthly variation of the relative frequencies of the reproductive phases of gonadal maturity and the mean GSI, for both sexes, it is suggested that the reproductive period of H. plumierii in the study area occurred from February to August, with a spawning peak between March to June. This spawning seasonality coincides with that reported from Jamaica (Munro et al, 1973), the Campeche Bank of Mexico (Darcy, 1983), Florida (Murie & Parkyn, 1999), Venezuela (Palazón-Fernández, 2007, and Brazil (Hoffmann et al, 2017;Shinozaki et al, 2013;Silva, 2015;Souza, 2008). Despite the differences in climatic seasonality between hemispheres, northern Figure 5.…”
Section: Discussionsupporting
confidence: 86%
“…In Florida, H. plumierii is mainly caught by hand and hook line (Murie & Parkyn, 2005;Padgett, 1997). It is one of the most representative fishery resources in Brazil (Hoffmann et al, 2017), as well as an important component in artisanal fisheries in several Caribbean countries, including Mexico (Araújo & Martins, 2007;Fernández et al, 2011;Palazón-Fernández, 2007;Potts & Manooch III, 2001;Shinozaki et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is indirect evidence that some members of the Haemulidae family form spawning aggregations in the west Indian Ocean [64] and the west Pacific Ocean [65]. While there is a lack of published information on the reproductive behaviour of any member of the Haemulidae, histological information from a western Atlantic Haemulid representative shows that, Haemulon plumieri collected from higher latitudes (> 17°) has a distinct spawning season [66, 67].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the weak governance structures of Brazil and most other developing countries (Pomeroy & Andrew, 2011), management of large tropical reef fishes is complicated due to their gregarious behavior and spawning aggregations, longevity, slow-growth, and late-maturation (Choat, Axe & Lou, 1996; Taylor & Choat, 2014; Taylor et al, 2018). Despite such challenges, biological data may be used to implement simple management measures (e.g., size limits, seasonal closures), and may also contribute to determine productivity and resilience to exploitation (Wooton & Smith, 2014; Aschenbrenner et al, 2017; Hoffmann et al, 2017).…”
Section: Introductionmentioning
confidence: 99%